The association between urinary BPA concentrations and urinary incontinence in women - Qian Lyu; Yu Nie; Jianyong Gao; Dong Wang (Scientific Reports)
Abstract Urinary incontinence (UI) significantly impacts the quality of life and psychological well-being of female patients. Although emerging evidence suggests potential links between endocrine-disrupting chemicals and pelvic floor disorders, previous studies on the association between bisphenol A (BPA) exposure and UI in women have yielded inconsistent results. This study aimed to examine this potential association using data from the 2015–2016 National Health and Nutrition Examination Survey (NHANES) (n = 467). Through multiple logistic regression analysis with three adjustment models: Model 1 (crude), Model 2 (adjusted for socio-demographic factors: age, race/ethnicity, education, marital status, and poverty ratio), and Model 3 (further adjusted for BMI, hypertension, diabetes, alcohol/smoking status, and delivery history), we assessed BPA exposure categorized into quartiles. No significant associations were observed between BPA exposure and either stress urinary incontinence (SUI) or mixed urinary incontinence (MUI) across all models (P > 0.05). However, participants in the highest BPA quartile (> 7.6 ng/mg creatinine) exhibited a significantly increased risk of urge urinary incontinence (UUI) in Model 1 (OR = 2.01, 95% CI [1.12–3.63]), Model 2 (OR = 2.04, 95% CI [1.08–3.85]), and Model 3 (OR = 2.48, 95% CI [1.18–5.20]). This study has several limitations, including its cross-sectional design, reliance on self-reported UI outcomes, single measurement of urinary BPA, and potential residual confounding from unmeasured factors. While these findings suggest that environmental BPA exposure may contribute to UUI risk in women, future longitudinal studies with repeated biomarker measurements and objective UI assessments are needed to confirm these observations and explore potential mechanisms. If validated, reducing BPA exposure through public health interventions could emerge as a novel preventive strategy for UUI.